Teaching Musical Education Lessons in the Pedagogical Universities (Texas Journal of Philology, Culture and History, 2023)
Literature, culture and art are of great importance for the young generation to deeply perceive the beauties of life and art, to develop their aesthetic sense and artistic taste. That is why the famous scientists and educators who created a unique school in the field of pedagogy and educational practice attached special importance to the knowledge that acquires aesthetic content and essence in the system of knowledge given to the young generation. They emphasized that every exercise related to aesthetic education has an effective effect on the development of a person.